Association of Physical Activity, Sleep Quality, and Vegetable and Fruit Consumption with the Risk of Diabetes Mellitus: A Case-Control Study in Biak Numfor, Papua, Indonesia - Febry Istyanto; Sophian Aswar (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Diabetes Mellitus (DM) is a major metabolic disorder marked by elevated blood glucose levels, which can result in severe health complications. In Indonesia, DM ranks among the top non-communicable diseases (NCDs), highlighting a significant public health crisis. Specifically, the Biak Numfor District in Papua is experiencing a marked rise in DM cases, threatening community health. Recent studies indicate that lifestyle modifications, dietary practices, and limited healthcare access significantly contribute to the rising urgency of addressing diabetes mellitus (DM) in specific regions. This research seeks to evaluate the risk factors influencing the incidence of DM through a multiple linear regression analysis model. Data was gathered from both diagnosed DM patients and a healthy control group in the Subdistrict of Sumberker, with 35 cases and 35 controls selected from each population. In this study, DM is the dependent variable, while the independent variables include physical activity, sleep quality, and the consumption of vegetables and fruits.Multiple linear regression analysis was used to determine the contributing factors to the incidence of DM in units. The results showed that regular physical activity contributed -0.26 units (P Value < 0.001); poor sleep quality contributed 1.7 units (P Value = 0.039). Meanwhile, regular vegetable consumption contributed -5.335 units (P Value = 0.004), and regular fruit consumption contributed -5.08 units (P Value = 0.002). This study concludes that regular physical activity and vegetable and fruit consumption lower the risk of developing DM, while poor sleep quality increases it.